2022
DOI: 10.1088/2631-8695/ac87eb
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SVR models for predicting the compaction properties of lateritic soils as novel hybrid methods

Abstract: Soil compaction and related parameters play a pivotal role in the material selection process for earth constructions. Because of time limitations and attention to completion resources, the need to develop models for predicting compaction properties is felt more than ever (i.e., maximum dry unit weight (γ_dmax) and optimum moisture content (ω_opt)) using easily measured index properties. The main purpose of this study is to evaluate the usefulness of conventional SVR, ensembled (additive regression (AD-SVR)), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Hasnat et al [24] applied Support Vector Machine (SVM) to develop a model for predicting the compaction parameters of soil. Zhu et al [25] used the Support Vector Machine (SVM), Additive Regression Support Vector Machine (AD-SVM), and Imperialist Competitive Algorithm Support Vector Machine (ICA-SVM) to predict the compaction parameters of lateritic soils, and the comparison showed that the ICA-SVM algorithm outperformed the other two algorithms. Sinha et al [16] used Artificial Neural Network (ANN) to develop a predictive model for compaction parameters and permeability of soils.…”
Section: Introductionmentioning
confidence: 99%
“…Hasnat et al [24] applied Support Vector Machine (SVM) to develop a model for predicting the compaction parameters of soil. Zhu et al [25] used the Support Vector Machine (SVM), Additive Regression Support Vector Machine (AD-SVM), and Imperialist Competitive Algorithm Support Vector Machine (ICA-SVM) to predict the compaction parameters of lateritic soils, and the comparison showed that the ICA-SVM algorithm outperformed the other two algorithms. Sinha et al [16] used Artificial Neural Network (ANN) to develop a predictive model for compaction parameters and permeability of soils.…”
Section: Introductionmentioning
confidence: 99%